2011
DOI: 10.1016/j.cmet.2011.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Receptor-Related Receptor as an Extracellular Alkali Sensor

Abstract: SUMMARY The insulin receptor-related receptor (IRR), an orphan receptor tyrosine kinase of the insulin receptor family, can be activated by alkaline media both in vitro and in vivo at pH>7.9. The alkali-sensing property of IRR is conserved in frog, mouse and human. IRR activation is specific, dose-dependent, quickly reversible and demonstrates positive cooperativity. It also triggers receptor conformational changes and elicits intracellular signaling. The pH sensitivity of IRR is primarily defined by its L1F e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
89
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(99 citation statements)
references
References 50 publications
(53 reference statements)
4
89
1
3
Order By: Relevance
“…Moreover, multiyear studies failed to discover any IRR agonist of the protein or peptide nature. Unexpectedly, recent studies revealed an unusual property of IRR to respond to an increase of extracellular medium pH (5,6). This finding suggests that the hydroxyl anion may represent a natural agonist of IRR (7).…”
mentioning
confidence: 92%
See 4 more Smart Citations
“…Moreover, multiyear studies failed to discover any IRR agonist of the protein or peptide nature. Unexpectedly, recent studies revealed an unusual property of IRR to respond to an increase of extracellular medium pH (5,6). This finding suggests that the hydroxyl anion may represent a natural agonist of IRR (7).…”
mentioning
confidence: 92%
“…BC117172) with full or partial ectodomain swapping were obtained by cloning using PCR strategy as described in Ref. 5. For generation of additional constructions with point mutations or with tyrosine kinase domain swapping, we used megaprimer PCR approach with mutated oligonucleotides.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations